How to promote empathy in games? An analysis of the structural elements to be considered in the interaction design - Galvão, Vinícius Ferreira; Maciel, Cristiano; Da Hora Rodrigues, Kamila Rios (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Empathic Games is a category of games that try to capture the reality of the characters and situations they face in order to make the player understand how it is to be "in someone else’s shoe". These are games that, in general, bring sensitive themes such as bullying, death, or various prejudices. There works that highlight the importance of empathy in games, yet there is very little on how games can foster empathy in the player. Through the literature review, we sought to find studies on how games can generate empathy and what games are considered empathic. After selecting the games, we analyzed their structural elements that can foster empathy, namely their: narrative, gameplay, graphics, and sound design. Our findings point out that the narrative element, alongside the intent and interdisciplinary factors (such as cultural aspects the game’s plot presents), are key factors in guiding how the game’s technical aspects support the player’s immersion in the game’s universe. We hope our results help in the development of interactive experiences that connect with the user on a deeper level, and allow them to better understand realities and scenarios that are different from their own daily lives. The findings of this study also complement the artifacts available in a conceptual framework to support designers and developers in creating more empathetic games.